Zur Bewertung von Niederdeutsch und lokalem Substandard in Hamburg - Schröder, Ingrid; Neumann, Lara (Linguistik Online, 2017)
Based on the results of a quantitative study it is to be shown how Low German and forms of the Substandard of Hamburg are estimated within the population. The study was conducted within the context of the project Einstellungen gegenüber regionalen Sprachformen in der Großstadt: Niederdeutsch in Hamburg (NiH) (Attitudes towards regional languages in the city: Low German in Hamburg). The article takes a closer look at the connection between evaluation and social parameters such as age, language skills, origin and education. Finally, the potential differences in the evaluation between Low German and the vernacular Hamburg speech will be examined.